Review on Management Information Systems (MIS) and its Role in Decision Making - Mishra, Sasanka S; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
he paper focuses on understanding the MIS philosophy, the need for MIS, the benefits of MIS in an organization, the MIS model, decisions and decision-making method, and MIS’s position in decision-making. This addresses MIS in brief considering the definition of MIS, the MIS model used by organizations, use of MIS, and need of MIS in organization. It then gives an overview of the decision making process and the decision-making system that is needed to understand the decision making process. Finally, the main focus of this paper is on the role MIS plays in an organization’s decision making. How to make decisions in an organization that uses MIS, what challenges the organization faces in this process and a few recommendations to curb these challenges. Management Information Systems (MIS) is an integrated, flexible and automated information system that deals with the process of collecting, processing, and distributing relevant information to support an organization’s management operations. In an organization, the data is distributed among the different departments.